High quality draft genome sequences of Pseudomonas fulva DSM 17717T, Pseudomonas parafulva DSM 17004T and Pseudomonas cremoricolorata DSM 17059T type strains. Issue 1 (December 2016) - Peña, Arantxa; Busquets, Antonio; Gomila, Margarita; Mulet, Magdalena; Gomila, Rosa; Reddy, T.; Huntemann, Marcel; Pati, Amrita; Ivanova, Natalia; Markowitz, Victor; García-Valdés, Elena; Göker, Markus; et al.
Abstract Pseudomonas has the highest number of species out of any genus of Gram-negative bacteria and is phylogenetically divided into several groups. ThePseudomonas putida phylogenetic branch includes at least 13 species of environmental and industrial interest, plant-associated bacteria, insect pathogens, and even some members that have been found in clinical specimens. In the context of theGenomic Encyclopedia of Bacteria and Archaea project, we present the permanent, high-quality draft genomes of the type strains of 3 taxonomically and ecologically closely related species in thePseudomonas putida phylogenetic branch:Pseudomonas fulva DSM 17717T, Pseudomonas parafulva DSM 17004T andPseudomonas cremoricolorata DSM 17059T . All three genomes are comparable in size (4.6– 4.9 Mb), with 4, 119– 4, 459 protein-coding genes. Average nucleotide identity based on BLAST comparisons and digital genome-to-genome distance calculations are in good agreement with experimental DNA-DNA hybridization results. The genome sequences presented here will be very helpful in elucidating the taxonomy, phylogeny and evolution of thePseudomonas putida species complex.